THE RELATIONSHIP BETWEEN STRESS AND NUTRITIONAL STATUS OF STUDENTS IN INDONESIA: A CROSS-SECTIONAL STUDY - Nurhazizah Br Said; Zata Ismah; Siti Aisyah (Journal of Community Mental Health and Public Policy)
Background: Nutritional status is the condition of the body caused by food intake and nutrient utilization. The categories of nutritional status are undernutrition, normal nutrition, and over nutrition. Nutritional status can be categorized in various ways, including using the body mass index (BMI). Purpose: was to determine the relationship between stress and nutritional status of university students. Methods: This research design used a cross-sectional design due to the analysis of this research which. The population in this study were students of the Faculty of Public Health, State Islamic University of North Sumatra. The sample was done by random sampling which amounted to 210 respondents. This research was conducted at the Faculty of Public Health, State Islamic University of North Sumatra in July 2024. The research data collected were processed using SPSS version 21 with Univariate and Bivariate tests. Collecting research data using the SRQ 29 (Self-Reporting Questionnaire) questionnaire developed by WHO. Results: There is a relationship between stress and the nutritional status of students (p-value = 0.003). Conclusion: Stress affects the nutritional status of students even though there are other factors that can affect the nutritional status of students such as diet, physical activity, and others